2015
DOI: 10.1016/j.acvd.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco, sport and the heart

Abstract: Smokeless tobacco (snuff) is a finely ground or shredded tobacco that is sniffed through the nose or placed between the cheek and gum. Chewing tobacco is used by putting a wad of tobacco inside the cheek. Smokeless tobacco is widely used by young athletes to enhance performance because nicotine improves some aspects of physiology. However, smokeless tobacco has harmful health effects, including cardiovascular disorders, linked to nicotine physiological effects, mainly through catecholamine release. Nicotine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
2
20
0
1
Order By: Relevance
“…Higher plasma catecholamine levels are associated with nicotine infusion during exercise and may lead to hemodynamic modifications effects that can compromise myocardial and muscular vascularization. Muscular strength may be impaired and the anaerobic threshold reached earlier [27]. Similarly, we also found that EC exposure decreased liver glycogen storage, in agreement with a previous study demonstrating that diabetic rats exposed to cigarette during pregnancy were impaired in their liver glycogen storage [28].…”
Section: Discussionsupporting
confidence: 92%
“…Higher plasma catecholamine levels are associated with nicotine infusion during exercise and may lead to hemodynamic modifications effects that can compromise myocardial and muscular vascularization. Muscular strength may be impaired and the anaerobic threshold reached earlier [27]. Similarly, we also found that EC exposure decreased liver glycogen storage, in agreement with a previous study demonstrating that diabetic rats exposed to cigarette during pregnancy were impaired in their liver glycogen storage [28].…”
Section: Discussionsupporting
confidence: 92%
“…[10,13] Regarding the use of smokeless tobacco (e.g. snus) or electronic cigarettes, products which allow the stimulating benefits of nicotine without impacting the respiratory capacity, [14,15] no information was available for examined athletes regarding their smoking habits. Up to now, snus products are not distributed in Italy and according to 2014 Annual Survey on Smoking Status of the Italian population just 1.6% of Italian smokers use electronic cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…This followed a study investigating athlete nicotine usage at the 2009 World Ice Hockey Championships (Marclay & Saugy, ) and seemed to reflect a trend of increasing nicotine usage in athlete populations as reported in other studies (Hu et al ., ; Morrell et al ., ; Alaranta et al ., ; Martinsen & Sundgot‐Borgen, ). While these studies did not investigate routes of administration, other studies suggest smokeless forms of tobacco (SLT) are gaining favour in athlete populations (Hu et al ., ; Alaranta et al ., ; Martinsen & Sundgot‐Borgen, ; Chague et al ., ). This increasing trend of SLT may in part reflect decreases in smoking practices amongst athletes (Morrell et al ., ; Alaranta et al ., ; Norberg et al ., ) while also representing a belief that SLT have performance‐enhancing properties (Chague et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…While these studies did not investigate routes of administration, other studies suggest smokeless forms of tobacco (SLT) are gaining favour in athlete populations (Hu et al, 1995;Alaranta et al, 2006;Martinsen & Sundgot-Borgen, 2014;Chague et al, 2015). This increasing trend of SLT may in part reflect decreases in smoking practices amongst athletes (Morrell et al, 2005;Alaranta et al, 2006;Norberg et al, 2011) while also representing a belief that SLT have performanceenhancing properties (Chague et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation